Pengaruh Fasilitas Wisata Dan Kualitas Pelayanan Terhadap Kepuasan Pelanggan Jasa Perjalanan Wisata (Open Trip) C.V Gass Adventure, Sidoarjo - Bayu Arista; Nur Aini Anisa; Nur Farida (FEB Universitas Maritim Semarang, 2023)
The purpose of this study was to determine the effect of tourist facilities and service quality partially on customer satisfaction for travel services C.V Gass Adventure, Sidoarjo. As well as to find out between the Tourism Facilities and Service Quality significantly influence Customer Satisfaction of C.V Gass Adventure Travel Services, Sidoarjo. This research was conducted using a questionnaire method using a sampling technique on 100 customers who are or have used C.V Gass Adventure travel services, Sidoarjo. The results of this study indicate that tourist facilities (X1) have a positive effect on customer satisfaction with a significance value of 0.02 which is smaller than the significance value of α of 0.05. Service Quality (X2) has a positive effect on customer satisfaction with a significance value of 0.04 which is smaller than the significance value of α of 0.05.